2022
DOI: 10.3390/cancers14163986
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Cuproptosis-Related Gene Signature for Prognostic Implication in Head and Neck Squamous Carcinomas

Abstract: Head and neck squamous carcinoma (HNSC) is a frequent and deadly malignancy that is challenging to manage. The existing treatment options have considerable efficacy limitations. Hence, the identification of new therapeutic targets and the development of efficacious treatments are urgent needs. Cuproptosis, a non-apoptotic programmed cell death caused by excess copper, has only very recently been discovered. The present study investigated the prognostic importance of genes involved in cuproptosis through the mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…We started by comparing the expression of a group of DEGs, or differentially expressed genes, in the two groups. We used the following rules by referring to previous studies [ 8 , 16 ]: if the LogFC (fold change) is greater than 1 or less than −1 (|logFC| > 1), we think that the gene is expressed significantly differently in the two risk groups. Furthermore, the FDR (false discovery rate) should less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…We started by comparing the expression of a group of DEGs, or differentially expressed genes, in the two groups. We used the following rules by referring to previous studies [ 8 , 16 ]: if the LogFC (fold change) is greater than 1 or less than −1 (|logFC| > 1), we think that the gene is expressed significantly differently in the two risk groups. Furthermore, the FDR (false discovery rate) should less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Cuproptosis is identified as a novel modality of mitochondrial cell death induced by dysregulation of copper homeostasis. Accumulating bioinformatic studies have indicated the involvement of cuproptosis in the immune infiltration of various malignancies such as pancreatic cancer, 7 gastric cancer, 8 lung adenocarcinoma, 9 renal cell carcinoma, 10 head and neck squamous carcinomas, 11 gliomas, 12 cutaneous melanoma, 13,14 cervical cancer 15 and endometrial carcinoma 16 . Cell death disorder has been identified to play an important part in the pathogenesis of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Intratumor copper can regulate the expression of PD-L1, affect the immune escape of tumours, and then affect the efficacy of immunotherapy [ 111 ]. Mutations in the mitochondrial ribosomal gene MRPS7 affect mitochondrial respiratory chain dysfunction, and high expression of MRPS7 is associated with poor prognosis in patients with HNSCC [ 112 , 113 ]. Studies have shown that high-dose Cu2 + exposure induces oxidative stress by increasing the levels of ROS and protein carbonyl compounds and reducing the GSH content and mRNA and enzyme activities, resulting in mitochondrial membrane potential depolarization, Cyto C release, cleavage of caspase-9 and caspase-3, increased BAK and BAX levels, decreased BCL2 levels and induction of tumour cell apoptosis [ 114 ].…”
Section: Mechanisms Of Cell Death In Hnsccmentioning
confidence: 99%